THE POLITICAL ANALYSIS OF THE R-ARCSS 2018, ON POWER SHARINGS - Thabo, Acwanyo Adam (IJRDO - Journal of Social Science and Humanities Research, 2021)
The paper investigates and analyses the Revitalized Agreement for the Resolution of the Conflict in South Sudan(R-ARCSS) which was signed on September, 12th 2018, Addis Ababa, Ethiopia. The agreement contains eight chapters and four annex, the paper focuses in analyzing the powers sharing chapter, which emphasizes a lot on power-sharing of different partners and signatories of the agreement including governmental, political parties among others, sharing of powers in percentage which SPLM/A ( ITGONU) 55%, SPLM/A ( IO)27%, SSOA= 10%, OPP= 8%, FDs= (0%), and participation of women’s should not be less than 35% in all governance level. It approximately (4,505) positions, headlined by president and five vice president, National Council of Ministers, National legislation Assembly and states governments, some was formed as government of transitional” period from all signatories, based on inclusivity. The parties also recognizes that Federal system of government is popular demand of people of South Sudan and democratic system of government within the permanent constitution-making process, and all this percentages will be dissolve after the interim period of three years started in 2018 and election should be done in 2021 . The chapter two is facing key tasks prior to the government’s formation would be training and unifying a new national army from among the armed groups and resolving the disputes over the number and boundaries of states to pave the way for local power sharing. In addition, the paper illustrates, observations, challenges and recommendation which may contribute on efforts of other scholars in the same filed of political analyses and issues related to power sharing in the region.